German Consumption Inequality. An evaluation with a focus on the financial crisis. - Katrin Heinrichs (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
How did the financial crisis impact on German demand? Are there significant differences in consumption behaviour depending on income? We analyse consumption data from 2005 to 2012/13 and find some indication for divergence of different income categories' consumption after 2009 and for a higher real interest rate sensitivity of higher income earners' consumption. Like in studies of income and wealth inequality, we also see a slight upward trend in consumption inequality that might have briefly staggered when the financial crisis hit.
Keywords: D31; D60; D30; 330